Relationship between symptom dimensions and white matter alterations in untreated patients with obsessive–compulsive disorder: a diffusion tensor imaging study. Issue 12 (12th August 2020) - Zhu, Jiahui; Li, Jinhao; Han, Yunyi; Liu, Wei
Abstract : The aim of the study was explore how the white matter structure changes and obsessive–compulsive disorder (OCD) symptom dimensions are related. We recruited 46 untreated adult patients with OCD, and 46 healthy controls matched for gender, age, and education. The patients were classified according to symptom dimensions assessed by the four-factor model. Diffusion tensor imaging (DTI) was employed to evaluate brain structural alterations in patients with OCD, and DTI data were processed using voxel-based morphometry (VBM) analysis. In comparison with healthy controls, there was a significant decreased fractional anisotropy of patients with OCD in several white matter regions of the cingulate gyrus and left inferior frontal gyrus. When stratified by symptom dimensions, patients presenting with the contamination/cleaning dimension had significantly lower fractional anisotropy in the white matter areas of the right insula and the left thalamus than the healthy controls. Whereas harm/checking symptom dimension patients exhibited a significant decrease of fractional anisotropy in the white matter regions of the right hippocampus. Our study has clear implications for the idea that OCD can be seen as a heterogeneous disorder, and symptom dimensions in patients with OCD are relevant to various white matter alterations patterns.